Total Bilirubin Is Associated with Small Intestinal Bacterial Overgrowth in Diarrhea Predominant Irritable Bowel Syndrome - Kim, So-Young; Seo, Young-Seok; Lee, Eun-Sub; Kim, Kyu-Nam (Annals of clinical and laboratory science, 2019)
Small intestinal bacterial overgrowth (SIBO) associated with irritable bowel syndrome (IBS) can cause microscopic mucosal inflammation and oxidative damage. Bilirubin is a marker of oxidant stress that is responsible for anti-oxidative activities. The objective of this research was to determine whether or not total bilirubin is associated with SIBO according to IBS subtypes. We retrospectively reviewed the charts of patients who showed IBS symptoms with documented results of lactulose breath test for SIBO. Multivariate models were used in order to assess the relationship of total bilirubin with SIBO according to IBS subtypes. In addition, we observed changes in total bilirubin when SIBO was treated with rifaximin in the relevant IBS subtype. The total bilirubin level of subjects with SIBO was significantly higher than it was in those without. An examination according to IBS subtype groups showed that total bilirubin was independently associated with SIBO only in the subjects with diarrhea-predominant IBS subtype (OR: 2.723, 95% CI: [1.303-5.692], <0.001). Additionally, a decrease in total bilirubin level and overall improvement of abdominal symptoms were observed following rifaximin treatment. These findings suggest that total bilirubin levels may provide additional information regarding the presence of SIBO in diarrhea-predominant IBS patients.